Predictors of success and failure in achieving glycemic control targets in patients with type 2 diabetes on basal insulin: review of the real-world evidence studies - V. V. Klimontov (Сахарный диабет)
Basal insulin (BI) is the main therapeutic option for patients with type 2 diabetes (T2D) who have not reached glycemic targets on oral antidiabetic drugs and/or glucagon-like peptide-1 receptor agonists. The results of epidemiological studies indicate that the majority of patients with T2D do not achieve the targeted parameters of glycemic control on BI in the real-world settings. In this review the results of real-world evidence studies assessing predictors of success or failure of BI therapy in patients with T2D are we summarized. A number of studies have demonstrated that delayed initiation of insulin therapy with a high level of glycated hemoglobin A1c (HbA1c) at the start of the treatment reduces achieving glycemic control targets on BI. Hypoglycemia in the first weeks or months of BI treatment may reduce the adherence and persistence to treatment and likelihood of achieving treatment targets. In real-world evidence studies, glargine 300 U/mL and degludec, the long-acting second-generation insulin analogues, have shown greater potential in reduction of HbA1c levels with a lower risk of hypoglycaemia compared to other BIs. In the DUNE, ATOS, and some others studies, a lack of insulin dose titration in newly initiated BI users and those who needed treatment intensification was demonstrated. Poor treatment adherence and persistence (missed injections, incorrect dose selection, and temporary or permanent discontinuation of insulin therapy), deviations in insulin injection technique, and formation of lipohypertrophy at the injection sites are also common problems that prevent good glycemic control in these patients. Therefore, patient education with a focus on injection technique, dose titration and prevention of hypoglycemia, as well as the use of the second-generation BI analogs, increases the chances for achieving glycemic control targets in patients with T2D who initiate or need to intensify BI therapy.